IL RILIEVO INTEGRATO: OCCASIONE DI APPROFONDIMENTO ED AGGIORNAMENTO PROFESSIONALE - Tucci, Grazia; Bonora, Valentina; Conti, Alessandro; Fiorini, Lidia; Nobile, Alessia (Archeomatica, 2012)
La richiesta di aggiornamento sulle più recenti tecnologie di rilievo ed acquisizione di dati tridimensionali ha indotto il Laboratorio di Geomatica del Dipartimento di Costruzioni e Restauro dell'Università degli Studi di Firenze ad organizzare il Primo Corso di Perfezionamento in "Geomatica per la Conservazione dei Beni Culturali”. Geomatics research group of DiCR Geomatics research group of DiCR – Department of Costruction and Restoration of University of Florence, held a Postgraduate Course in "Geomatics for Cultural Heritage Conservation” that ran from January to April 2010. Course contents was: Measure and Architecture, 3D Scanning Systems, Laser Scanning and 3D Modelling, Digital Close Range Photogrammetry, Termography and Metric Survey at Urban Scale and Digital Cartography. In addition to lectures, there was laboratories on data acquisition, evaluation and processing. Final workshop took place in Villa Demidoff at Pratolino, with regard of cooperation agreement between DiCR and Florence Provincial Council. Survey concerned the Paggeria exterior and façade and the Chapel by Buontalenti. Survey project was briefed to make as effective as possible the use of all different acquisition and 3D data processing techniques studied during lectures. The course will be replied on 2011.